Феномен русской прозы: писатели – референты иноэтнокультуры - Eleonora Szafranskaja (Studia Rossica Posnaniensia)
The contemporary literature borders don't agree with the formal state borders. The Russian literature is an example of this. Its ethnic index doesn't correspond either with a writer's residence or his citizenship. Belonging to the Russian literature is defined by the Russian language. Some of non-Russian ethnic writers win awards for their contribution to the Russian literature. Thus any author writing in Russian is a Russian writer. By origin and nurture D. Rubina, T. Pulatov, S. Aflatuni, CH. Aytmatov, A. Volos et al. belong to the Russian culture as well as to a non-Russian one. Being in the sphere of folk and family mythology, memories, traditions, ethnic cooking, religious myths, these writers create their non-Russian ethnic works in Russian. They appear as commentators, interpreters, mediators between two mentalities: the own and the non-own, acting as spokesmen for non-Russian ethnic culture, or as translators between different mentalities, different ethnic values.